2006
DOI: 10.1159/000088559
|View full text |Cite
|
Sign up to set email alerts
|

Does Insulin-Like Growth Factor 1 Contribute in Red Blood Cell Transfusions to the Pathogenesis of Retinopathy of Prematurity during Retinal Neovascularization?

Abstract: Background: Red blood cell (RBC) transfusions are associated with the development of retinopathy of prematurity (ROP). During the period of retinal neovascularization a rise of insulin-like growth factor 1 (IGF-1) may trigger rapid growth of new blood vessels. Objectives: To study endocrine factors in RBC transfusions that might be of importance for ROP. Methods: IGF-1, IGF-2 and their binding proteins 1–3 (IGFBP-1–3) were determined by radioimmunoassays in 7 very-low-birthweight (VLBW) infants with ROP ≧ stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
5
1
Order By: Relevance
“…Our previous studies have demonstrated that a prolonged period of a low level of serum IGF-I in children born preterm is strongly associated with ROP. 4 Hubler et al 14 and Villegas Becerril et al 15,16 have confirmed this association. Poor postnatal weight gain has also been suggested as a risk factor for the development of severe (Նstage 3) ROP.…”
Section: Commentmentioning
confidence: 84%
“…Our previous studies have demonstrated that a prolonged period of a low level of serum IGF-I in children born preterm is strongly associated with ROP. 4 Hubler et al 14 and Villegas Becerril et al 15,16 have confirmed this association. Poor postnatal weight gain has also been suggested as a risk factor for the development of severe (Նstage 3) ROP.…”
Section: Commentmentioning
confidence: 84%
“…Only oxygen administration and the number of hemotransfusions were significantly correlated with both free IGF-I and PAPP-A molecules and their ratio. The biological and clinical implications of a red blood cell transfusion given to premature infants in terms of IGF-I load have recently been underlined (21). Of course, ELF IGF-I levels measured in our patients during the first 4 days of life are not dependent on hemotransfusions, since these were only administered after this period.…”
Section: Epithelial Lining Fluid Levels Of Free Igf-i Papp-a and mentioning
confidence: 79%
“…A large number of risk factors have been implicated in the aetiology of ROP (10–21): prematurity, birthweight, ethnic background, oxygen levels, hypercapnia, concomitant illness or disease (sepsis, bronchopulmonary dysplasia and intraventricular haemorrhage), acidosis, indication for blood transfusion, ambient light levels, erythropoietin treatment, vaginal birth, etc.…”
Section: Introductionmentioning
confidence: 99%